Studi Putusan Nomor 26/Pdt.G/2022/Pn Ngb Tentang Gugatan Kepemilikan Hak Atas Tanah - Tamarin Tambunan, Ade; Pahlefi, Pahlefi (Universitas Jambi, Fakultas Hukum, 2025)
This study aims to analyze the basis of the judge's consideration and its implications for legal certainty in Decision Number 26/Pdt.G/2022/PN NGB regarding land ownership disputes that have not been reversed. The research method used is normative juridical by collecting primary, secondary, and tertiary legal materials. The results of the study show that the basis of the judge's consideration has juridical weaknesses because it ignores Articles 1320 and 1472 of the Civil Code, which states that the sale and purchase of land should be void if the object does not belong to the seller. In addition, Article 37 of Government Regulation No. 24 of 1997 which requires a Deed of Sale and Purchase from PPAT and Article 64 of Government Regulation No. 18 of 2021 concerning an objection period of 5 years are also not considered. Sociologically, this decision provides temporary legal certainty for the Plaintiff, but still risks causing new disputes. Philosophically, this decision prioritizes formal legal certainty over substantive justice. In conclusion, a process of changing the name and the Deed of Sale and Purchase at PPAT is needed to ensure stronger legal certainty.